Influence of the Guided Discovery Learning Model on Primary School Students' Mathematical Problem-solving Skills - Lubis, Akhmad Badrul; Miaz, Yalvema; Putri, Indah Eka (Universitas Pendidikan Indonesia, 2019)
Difficulties of primary school students in solving mathematical problems that require problem solving or reasoning abilities indicate the existence of problems in the process of learning mathematics, because one of the purposes of learning mathematics in primary school is to develop the students mathematical problem-solving skills. As a solution to overcome the problems, this research aims at understanding how the implementation of the guided discovery learning model influences mathematical problem-solving skills. This research employs a quasi-experimental design by involving all fifth-grade students at one of primary schools in Tebo Regency, Jambi. The simple random sample was conducted to obtain class VB as experimental class, and class VA as control class. Based on the results of the final score, experiential class obtained an average score of 86.00, and control class obtained an average score of 76.93. The results of hypothesis test using t-test obtained tcount = 2,203 ttable = 2,020, which indicated that H0 was rejected, and H1 was accepted. Therefore, the guided discovery learning model influenced the fifth-grade students mathematical problem-solving skills, thus it is recommended for teachers to be able to use the guided discovery learning model in the mathematics learning process.